Changing Trends in Peripartum Hysterectomy at Tertiary Institute in Nepal - Bista, KDB (Journal of Institute of Medicine Nepal, 2014)
Introduction: Peripartum hysterectomy refers to hysterectomy done during or immediately after delivery for obstetrical reason. The decision of hysterectomy is not an easy one as not doing it could lead to death whereas the surgery results in permanent loss of ability to bear a child and this too in a young woman. Methods: This was a prospective study done over a period of 16 years from 1997 to 2013 by following all cases that underwent hysterectomy for obstetric causes during or after delivery and up to 6 weeks after delivery, in Department of Obstetrics and Gynecology, Tribhuvan University Teaching Hospital, Nepal. The various factors were analyzed and data presented in percentages, means and odds ratio was calculated as necessary. P value less than 0.05 was taken as significant. Results: The emergency peripartum hysterectomy rate was 0.05%. Placental abnormality was the most common indication (42.6%) followed by uterine atony (35.7%) and uterine trauma (17.9%). Cesarean Hysterectomy accounted for 50% of the cases. In the last 16 years there was an increased trend of Cesarean section from 18.6% to 30.7% which coincided with an increased Cesarean Hysterectomy from 36.4% in the initial 8 years to 58.8% in the last 8 years. Placental abnormalities as an indication increased over uterine atony in the last 8 years. The most common risk factor was Cesarean section (71.4%) followed by placental abnormalities (42.8%) and previous abortion in 32.1% cases. Conclusion: Emergency Peripartum Hysterectomy rate was 0.05%. Increasing Cesarean section rates were associated with increasing Cesarean Hysterectomy rates.